Marketing Strategy of The Pink Mete Product (Anacardium Occidentale L.) in The Home Industry in The Continental District of Muna - Rizal, Muahammad; Karimuna, La; Herdhiansyah, Dhian (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
This study aims to: (1) Learn how the processing of cashew products in the home industry (2) Learn what strategies are implemented to increase sales of cashew products in the home industry. This research has been conducted since January 2019. The population in this study is the whole cashew home industry. Sampling is done by